Go hand in hand: Showcasing lecturers’ online collaborative teaching practices - Maolida, Elis Homsini; Sofarini, Anisa (Indonesian Journal of Applied Linguistics, 2022)
Collaborative teaching has been performed by special educators in K-12 schools for decades, and myriads of studies have witnessed its promising impacts on both students and teachers. Notwithstanding its vogue, only a few studies have primarily dealt with its implementation in higher education. Furthermore, empirical attempts accentuating lecturers’ stepwise practices during collaborative teaching implementation remain under-explored, especially when the practices are undertaken online. This study, henceforth, intends to fill the void. In total, the experiences of two collaborating lecturers, leading Teaching English for Foreign Language (TEFL) and Technology-Enhanced Language Learning (TELL) course, were scrutinized. Their practices were documented for 20 weeks and their views were also assembled to grasp how they perceived their online co-teaching practices. In addition, the views from six representative students were assembled at the end of the term through focused group discussion. Through Joint Practice Development (JPD) framework, lecturers’ online collaborative teaching practices were captured and conceptually grouped into five developed stages – collaborative planning, collaborative instruction, peer feedback and evaluation, follow up, and refinement stage. Admitting lecturers’ online co-teaching approach, students contended that its implementation was opportune in bridging their needs of pedagogical knowledge and related technology, facilitating learning efficiency, and fostering their collaboration awareness. Albeit its effectiveness, students are also concerned with collaboration appearance clarity, learning proficiency, and autonomy. Thus far, this teaching approach is worthy of continuing in the higher education, with clear format to adopt.